Socialization of Prevention of Escherichia coli Bacterial Contamination in Well Water in Sidanegara Village as a Stunting Countermeasure - Imam Agus Faizal; Dini Puspodewi; Frisca Dewi Yunadi; Ira Pangesti; Mika Tri Kumala Swandari (Jurnal Pengabdian Pancasila (JPP), 2024)
Human health can be directly affected by water quality if E. Coli bacteria are found. Most residents of Cilacap Regency get their drinking water from wells, cooking, washing household appliances, and poor sanitation behavior. This method of community service in health counseling is divided into several stages of implementation. These stages include pre-service surveys and counseling. The results of the pre-test with the theme Identification of E. coli Bacteria Contamination as a Stunting Response were obtained with an average cadre knowledge score of 86. Meanwhile, the average score of the post-test questionnaire was 93. The conclusion of the results of this service is the results of the pre-test and post-test of the cadres which have experienced a significant increase in cadre knowledge.